1997
DOI: 10.1016/s0741-5214(97)70217-9
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy for recurrent stenosis

Abstract: Although repeat endarterectomy to treat RCS is technically more demanding, it can be performed safely. Long-term follow-up examination shows that a second recurrence may develop, and we recommend serial noninvasive testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 25 publications
4
56
0
4
Order By: Relevance
“…This number compares favorably with other similar studies. Mansour et al 10 reported transient or permanent cranial nerve deficits in 7.3% of redo CEAs, whereas Zarins 28 reported the incidence of cranial nerve palsies to be as high as 20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This number compares favorably with other similar studies. Mansour et al 10 reported transient or permanent cranial nerve deficits in 7.3% of redo CEAs, whereas Zarins 28 reported the incidence of cranial nerve palsies to be as high as 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of recurrent carotid stenosis after primary CEA ranges from 10% to 25%. [3][4][5][6][7][8][9][10][11][12] Reoperation has been considered necessary in only 1% to 8% of cases. [3][4][5][6]12 Given that there has been an overall increase in the number of primary CEAs being performed, it follows that the total number of reoperations will also increase.…”
mentioning
confidence: 99%
“…The decision to perform surgery on patients with symptomatic or asymptomatic restenosis should be performed with the knowledge that there is an increased risk of stroke and death, as well as an increased risk of local complications such as cranial nerve injury and wound hematoma. 33 The increased operative risk may be due to differences in pathology between primary atherosclerotic stenosis and early restenosis, which is commonly due to smooth myointimal hyperplasia, rather than atherosclerotic plaque. 30,34,35 The issue of risk of CEA in relation to the timing of surgery can be separated into the question of the risk of surgery in the acute phase (ie, in patients with stroke in evolution and crescendo TIAs) and whether the risk of surgery differs between the subacute phase (first few weeks) and the nonacute phase in those patients who are neurologically stable.…”
Section: Discussionmentioning
confidence: 99%
“…The use of patches is not well established yet. 31,32 We think the selective use of patches in small-caliber arteries, as done in this series, is adequate.…”
Section: -14mentioning
confidence: 78%